Conversations between the living and the dead – Wills in 19th century literature (KULT_online, 2014)
Ulrike Vedder analyses last wills in the context of law, economics, and culture as well as regarding concepts of inheritance reforms during the 19th century in Western Europe. On the basis of numerous examples she convincingly demonstrates how 19th century literature (from Jean Paul, Kleist, E.T.A. Hoffmann, Balzac, Heine, Droste-Hülshoff, Stifter, Melville, Keller, Storm, Fontane, Zola, James) participated in social reform debates concerning the variety of inheritance laws in West Europe.